Dick Prescott's Fourth Year at West Point : Or, Ready to Drop the Gray for Shoulder Straps - Hancock, H. Irving (Harrie Irving), 1868-1922 (Salt Lake City, UT : Project Gutenberg, 2004)
"Dick Prescott's Fourth Year at West Point" by H. Irving Hancock is a novel likely written during the early 20th century. The story follows Cadet Richard Prescott, now a first-classman at the United States Military Academy, as he encounters the trials and tribulations of military training, camaraderie, and class politics during his final year before graduation. The narrative centers around Prescott's character as a leader and how his adherence to duty and principles leads to conflict, particularly with Cadet Jordan, who seeks revenge after being reported for his indolence. The opening of the novel sets the stage for Prescott's leadership during a military engineering exercise, where he is challenged by the lazy conduct of his classmate Jordan. As Prescott assigns duties for constructing a pontoon bridge, he faces both logistical challenges and personal rivalries. Tensions rise as Jordan's resentment leads to a series of retaliatory schemes against Prescott, culminating in class divisions and an official silence imposed by their classmates. The narrative provides insight into cadet life, leadership responsibilities, and themes of honor and loyalty, while hinting at further conflicts as the class navigates the challenges of military discipline and personal relationships. (This is an automatically generated summary.)
Release date is 2004-07-03
Produced by Jim Ludwig
Keywords: College stories; United States Military Academy -- Juvenile fiction; Military cadets -- United States -- Juvenile fiction